Cultural Immersion for International Students: APath to Promoting TorajaTourism - Limbongan, Mey Enggane; Ardiyanti, Wilma Dian; Patadungan, Ellyn; Panimba, Marniati Winta; Salu, Angelia (Jurnal Literasiologi, 2024)
This study explores the role of cultural immersion programs conducted by the Tourism Study Program at UKI Toraja in promoting Toraja tourism. This study employs a qualitative research design, focusing on an in-depth exploration of the experiences of international students who participated in cultural immersion programs in Toraja. A case study methodology was chosen to provide a detailed examination of a specific instance of cultural immersion, making it possible to identify the key elements that contribute to its effectiveness in promoting tourism. The study involves international students who participated in cultural immersion programs organized by the Tourism Study Program at UKI Toraja. Participants were selected through purposive sampling to ensure that those included in the study had direct and substantial experiences with Toraja culture. Semi-structured interviews were conducted with both international students and local community member. The researcher engaged in participant observation during several cultural immersion activities, including traditional ceremonies, community events, and daily interactions between students and local residents. The data collected from interviews and observations were analyzed using thematic analysis. The study results confirm that the cultural immersion programs conducted by the Tourism Study Program at UKI Toraja play a significant role in promoting Toraja tourism by enhancing cultural understanding and intercultural competence, fostering personal and academic growth, and positioning students as cultural ambassadors.